Enhancing the role of health cadres in stunting prevention in the Munjul region through elderly support for breastfeeding: A participatory action research - Deswani, Deswani; Mulyanti, Yuli; Djuwitaningsih, Sri; Syafdewiyani, Syafdewiyani; Siti, Eros (Science Center Group, 2025)
Background: Stunting remains a major public health problem in Indonesia, particularly in urban communities with limited resources and suboptimal breastfeeding support. Health cadres play a strategic role in maternal and child health programs; however, their effectiveness can be enhanced through innovative approaches that actively involve community members, including the elderly, as breastfeeding support agents. This study aimed to evaluate the impact of a health cadre training program that empowered elderly groups as breastfeeding support agents in preventing stunting. Methods: A Participatory Action Research (PAR) design was employed involving 47 participants, consisting of health cadres and elderly community members. Participants were selected using purposive sampling based on their active involvement in maternal and child health activities. The intervention comprised structured training sessions covering exclusive breastfeeding, balanced nutrition, breastfeeding techniques, breast care, and child growth monitoring. Data were collected using pre-test and post-test questionnaires, observations, and focus group discussions. Quantitative data were analyzed using descriptive statistics and paired t-tests. Results: The findings demonstrated a significant improvement in participants’ knowledge following the intervention. The mean pre-test score was 77.56 (SD = 8.46), which increased to 84.65 (SD = 8.46) in the post-test assessment. The training also strengthened collaboration between health cadres and elderly participants, enhanced community engagement in breastfeeding support activities, and increased participation in child growth monitoring. Conclusion: Empowering health cadres through elderly-supported breastfeeding training effectively improved knowledge and community involvement in stunting prevention. Integrating elderly groups into community-based breastfeeding support initiatives represents a promising and sustainable strategy to strengthen maternal and child health programs and reduce the risk of stunting.